Acute and sub-chronic toxicity of glucose–cysteine Maillard reaction products in Sprague-Dawley rats. (June 2015) - Li, Yixing; Su, Linliang; Li, Fenfang; Wang, Chaozheng; Yuan, Debao; Chen, Jiao; Tan, Lin; Jin, Zhiqiang; Ma, Weihong
Highlights: Glucose–cysteine Maillard reaction products (MRPs) are valuable food additives with excellent anti-browning effects. We investigated the in vivo toxicity of MRPs following acute and sub-chronic administration in rats. The acute LD50 of glucose–cysteine MRPs in rats was 6.81 g/kg. Repeat 90-day administration of less than or equal to one-fifth LD50 produced no significant toxicities. Abstract: Maillard reaction products (MRPs) derived from glucose–cysteine reactions have excellent anti-browning ability. However, there is a lack of information about their acute and sub-chronic toxicities. To our knowledge, the present study is the first to evaluate the acute and sub-chronic toxicities of MRPs in experimental animals. Acute toxicity testing and analysis by Horn's method showed that the median lethal oral dose (LD50 ) of MRPs in rats was 6.81 g/kg body weight. The sub-chronic toxicity test involved feeding rats with diet containing 0, 0.43, 0.85, or 1.70% (w/w) MRPs for 90 days. These treatments did not affect mortality, gross pathology, histology, hematology, or blood chemistry, and there were no dose-dependent changes in feed consumption. Based on these results, the dietary no-observed-adverse-effect level (NOAEL) for 90-day exposure was 1.29 and 1.51 g MRPs/kg body weight/day for male and female rats, respectively.